Salinização secundária em solos do distrito irrigado do baixo-açu, em alto do rodrigues/rn - Andrade, Ayslann Tôdayochy Siqueira de (Universidade Federal Rural do Semi-Árido, 2019)
The Irrigated District of Baixo-Açu (DIBA) is an agricultural area of great importance for irrigated fruit growing in the state of Rio Grande do Norte, mainly in banana production. However, due to the climatic characteristics of the region, since the area is under semi-arid climate, where there are high rates of potential evapotranspiration and low rainfall rates, inadequate management of irrigation and the use of irrigation water of inferior quality, has contributed to the process of salinization of soils, affecting the growth of certain crops, reflecting, consequently, the productivity of the areas. Thus, the objective of this work was to evaluate the secondary salinization process of the soils in a watershed in the DIBA, as well as the behavior of the salts along the profiles of the analyzed soils. Soil samples were collected in five areas (Lot 1, 2, 3, 4 and Mata Nativa (MN)) in May, July and September of 2018, selected according to altitude, in a watershed, in the 0-20 and 20-40 cm soil layers, for the procedure of the physical analyzes (particle size, soil density, particle density) and chemical analyzes (pH, CEes, P, K+, Na+, Ca2+, Mg2+, CTC, SB, PST). In addition, water samples were collected at six distinct points (P1, P2, P3, P4, P5 and P6) in the watershed, during the same period in which the soil samples were collected, to determine the chemical analyzes (CE, pH, Na+, Ca2+, Mg2+, K+, Cl-, CO32- e HCO3-). Data were submitted to descriptive statistics as mean, standard deviation, maximum value and minimum value. Therefore, the results of soil chemical analyzes were submitted to multivariate statistics, such as correlation matrix, factorial analysis, cluster analysis and analysis of main behaviors. The results indicated that, during the period of study, accumulation of salts in the soil occurred in all lots analyzed, which the 0-20 cm layer being the most affected by the salts. The highest concentrations of salts in the soil occurred at the end of the dry period (November). All lots analyzed were classified as normal soils, except for lot 4, which was classified as saline soil, proving what was observed in the field, being necessary the adoption of drainage system and the washing of salts. The ions that contributed most to the soil salinization were Na+ and Mg2+, pH and PST exerted a strong influence as well.
Keywords: Solos agrícolas; Irrigação; Semiárido brasileiro; Microbacia hidrográfica; Agricultural soils; Irrigation; Brazilian semi-Arid; Watershed; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO